METODE SEBAGAI MOTIVASI EKSTRINSIK BAGI SISWA DA LAM PROSES PEMBELAJARAN - Endah, Retno (MAJALAH ILMIAH PEMBELAJARAN, 2007)
Motivation is a feeling that causes action. There are 2 variaties of motivation: in1rinsic and extrinsic motivation. An intrinsic motivation is motivC’lion that comes from him self In contrast, an extrinsic motivation is motivation that comes from out side. In the learning process not all of the learners have the motivation of learning. Some of them have hight motivation, but a few of them have low motivation or do not have any motivaton. The hight motivation learners usually participate the learning process with hight spirit and enjoy 1he learning process. But the learners, that have no motivation will not participate the learning process and sometimes leave the class and will do an:>ther interested activities. In this case the teacher must find the solution to give motivation to · the learner, for examvle using the special methods in the learning process, so that the learner can be motivated We hope that by using the methods it can makes the learner participate the learning · process with the spirit. But the teacher must choose the methods that are suitable with the learner competency, learning material, the learner self. the teacher, the situation and the condition of the class.